Relation extraction in vietnamese text using label propagation. - Rathany, Sam Chan; Hương, Lê Thanh; Thủy, Nguyễn Thanh; Long, Nguyễn Thành; Dũng, Trịnh Minh (Journal of Computer Science and Cybernetics, 2014)
This paper presents a relation extraction system for Vietnamese texts using label propagation. In this paper, we propose: (i) a measure of similarities between two sentences; (ii) a method to decrease the effect of high frequency labels in the documents. Our experimental results show that proposed label propagation method achieves a higher accuracy than the ordinary one [10]. Moreover, its accuracy is also higher than the support vector machine method applied.